Maternal genetic polymorphisms of phase II metabolic enzymes and the risk of fetal neural tube defects. Issue 1 (4th December 2013) - Wang, Linlin; Jin, Lei; Liu, Jufen; Zhang, Yali; Yuan, Yue; Yi, Deqing; Ren, Aiguo
<x xml:space="preserve">Abstract</x> Background Maternal exposure to polycyclic aromatic hydrocarbons (PAHs) has been associated with the risk of fetal neural tube defects (NTDs). Whether maternal genetic variants related to PAH metabolism contribute to the development of fetal NTDs remains unclear. Methods We conducted a case–control study in a Chinese population to examine the association of selected maternal genetic variants of phase II enzymes involved in the elimination of the metabolic intermediates of these chemicals with fetal NTD risk, and to evaluate possible interaction of the genetic variant and maternal exposure to indoor air pollution from coal combustion and smoking (IAPCC). Blood samples were collected from 534 NTD case mothers and 534 control mothers and assayed for 12 polymorphisms of 5 genes encoding phase II enzymes. Results We found that the rs9282861 GG genotype of SULT1A1 was associated with an elevated risk of total NTDs (odds ratio [OR] = 2.12, 95% confidence interval [CI]: 1.49–3.00), compared with the GA genotype. The SULT1A1 rs9282861 variant showed a significant additive interaction with maternal exposure to IAPCC for NTD risk, with a relative excess risk of interaction of 1.20 (95% CI 0.23–2.18), and the OR for the joint effect of high‐level IAPCC exposure and the GG genotype was 8.37 (95% CI: 3.63–19.28). Conclusion Maternal SULT1A1 polymorphism is associated with the risk of fetal NTDs, and has an additive‐scale interaction with maternal IAPCC exposure for NTD risk. Birth Defects Research (Part A) 100:13–21, 2014. © 2013 Wiley Periodicals, Inc.